Long-term non-institutionalized survival and rehospitalization after surgical aortic and mitral valve replacements in a large provincial cardiac surgery centre. (14th February 2018) - Yan, Weiang; Shah, Pallav; Hiebert, Brett; Pozeg, Zlatko; Ghorpade, Nitin; Singal, Rohit K; Manji, Rizwan A; Arora, Rakesh C
Abstract: OBJECTIVES: Long-term quality of life following open surgical valve replacement is an increasingly important outcome to patients and their caregivers. This study examines non-institutionalized survival and rehospitalization within our surgical aortic valve replacement (AVR) and mitral valve replacement (MVR) populations. METHODS: A retrospective single-centre study of all consecutive open surgical valve replacements between 1995 and 2014 was undertaken. Clinical data were linked to provincial administrative data for 3219 patients who underwent AVR, MVR or double (aortic and mitral) valve replacement with or without concomitant coronary artery bypass grafting (CABG). Non-institutionalized survival and cumulative incidence of rehospitalization was examined up to 15 years. RESULTS: Follow-up was complete for 96.9% of the 2146 patients who underwent AVR ± CABG (66.7% of the overall cohort), 878 who underwent MVR ± CABG (27.3%) and 195 who underwent double (aortic and mitral) valve replacement ± CABG (6.0%) with a median follow-up time of 5.6 years. Overall non-institutionalized survival was 35.4% at 15 years, and the cumulative incidence of rehospitalization was 34.4%, 63.2% and 87.0% at 1, 5 and 15 years, respectively, without significant differences between valve procedure cohorts. Both non-institutionalized survival and cumulative incidence of rehospitalization improved in more recent eras, despite increasing age and comorbidities. CONCLUSIONS: Non-institutionalized survival and rehospitalization data for up to 15 years suggest good functional outcomes long after surgical AVR and/or MVR. Continued improvements are seen in these metrics over the past 2 decades. This provides a unique insight into the quality of life after surgical valve replacement in the ageing demographics with valvular heart disease.